Navigating perinatal mental health integration in maternal and child health services: progress and priorities for research and practices in Pakistan - Waqas Hameed; Atif Rahman (BJPsych International)
We synthesise perinatal mental health (PMH) evidence and provide recommendations for future research and practices in Pakistan. The burden is significantly higher relative to many other countries, with adverse effects on women and children. Few locally developed interventions involving non-specialists have shown promise, but integrating these into maternal and child health services (MCH) at scale remains a challenge. We recommend broadening the scope of PMH research in accordance with the World Health Organization's stepped care model, and advancing the use of implementation science, digital technology and exploring low-cost models. Programmes and policies should prioritise incorporating PMH into MCH services in health planning and budgeting.